Exploring The Impact of Causes Of Burnout on Motivational Elements in Learning Mathematics - Siti Salwana, Mamat; Zarith Sofiah, Othman; Suhalia, Safiai; Nor Azahariah, Mohamad; Amirul Aizad, Ahmad Fuad; Noor Hanim, Rahmat (Human Resource Management Academic Research Society (HRMARS), 2023)
The prevalence of burnout among students has emerged as a significant concern in educational settings, leading to adverse effects on their motivation, academic performance, and overall engagement. To investigate this issue, a quantitative survey study was conducted to explore how burnout impacts the motivational aspects of learning mathematics among pre-university students. The study's primary objectives were to understand how learners perceive motivational elements in their math education, identify the root causes of burnout, and examine the relationship between motivational factors and burnout experiences. The data were collected using a questionnaire. The questionnaire focuses on getting responses regarding the instrument, which comprises three sections: the demographic profile, three key components of motivational elements (value, expectancy, and affective), and two components of burnout causes (exhaustion and disengagement) using a 5-point Likert scale. A total of 119 respondents from the Foundation in Science and Engineering programmes at the Centre of Foundation Studies, UiTM Cawangan Selangor, participated in the survey. The findings revealed that students who displayed a comprehensive grasp of foundational mathematics demonstrated higher levels of satisfaction and enthusiasm for acquiring new knowledge, prioritising meaningful learning experiences over mere grade attainment. Notably, the correlation analysis indicated a highly significant association between motivational elements and burnout causes, highlighting the interconnected nature of motivation and burnout. Furthermore, the results indicated that students exhibited a strong intrinsic goal orientation, valuing opportunities to gain knowledge and skills in mathematics. However, certain factors, such as reading difficulties and a lack of support, contributed to burnout and diminished motivation. Addressing these factors becomes crucial to cultivating a positive learning environment and enhancing students' performance in mathematics. The implications of this study extend to educators and policymakers, who can leverage these findings to develop strategies and interventions that foster student motivation, alleviate burnout, and promote engagement and achievement in mathematics. By addressing the identified burnout causes and enhancing motivational aspects, educational institutions can create a conducive and empowering learning environment for students, ultimately leading to improved academic outcomes and overall well-being.